Madrasah Head Supervision In Improving The Teaching Quality of Pendidikan a Teachers In Madrasah Ibtidaiyah Negeri 1 Boyolali - Sumadi; Meti Fatimah (Didaktika: Jurnal Kependidikan, 2024)
This research aims to determine the supervision of the Madrasah heads in improving the teaching quality of Islamic religious education teachers at MIN 1 Boyolali. This research is a qualitativeresearch. This research was conducted at MIN 1 Boyolali from October to December 2023. The subjects in this research were the school principal, Islamic Religious Education Teacher, curriculum sie and students of Madrasah Ibtidaiyah Negeri 1 Boyolali. Data was obtained using participant observation, structured interviews, and documentation. Data analysis uses the Miles and Huberman analysis model called interactive analysis. This analysis is divided into several stages: data collection, data reduction, data presentation, and drawing conclusions. The results show that the Madras head as a supervisor carries out supervision with guidance, supervision and guidance. There are supporting and inhibiting factors in implementing supervision. To address the inhibiting factors, madrasah heads need to continue to monitor developments in educational policies and adjust supervision practices according to applicable policies. Meanwhile, the supporting factor is a clear understanding of the purpose of supervision. All parties in the school, including teachers and staff, clearly understand the objectives of the Madras head's supervision, this helps create a common focus in efforts to improve performance.